(3eNJUQ JGQjN eUQs - (3GdMSf Hf EHQGgje Hf GdMSjf Hf GdMSf, ef hdO SdjeGf GHf RhdGb, GddjKj HGdhdGA, CHh eMeO,J (B387 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO GdMSf gPG cJGH LeYJ ajg LedI ef CNHGQ eUQ haVGFdgG hUaJgG , GNJUQJg ef cJGH (B( (3i(B) (3GdcHjQ ai JGQjN eUQ hGNHGQgG s
(3BNQgG (B:s
(3cGfJ GdMceGA JMO ajg GdCSaGQ hajg jYed GdNd ajchf UGdMkG hjHJOF ajg EOQGQ GdQeGf hGddg JYGdi CYde s
(3HOGNdgG NQe ef hQbI (B30 _46 (3eced Hbde MOjK LOkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B194s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B172 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs